Media Sosial sebagai Ruang Belajar dan Tantangan Moral Siswa di PKBM Abu Bakar Ash-Shiddiq - Harjanti Harjanti; Imas Masripah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines social media as a student-centered learning space and its moral implications in a nonformal education context, specifically at PKBM Abu Bakar Ash-Shiddiq. Previous studies have largely focused on the instructional effectiveness of social media, while limited attention has been given to its ethical and character-related dimensions in nonformal learning environments such as community learning centers. This research employed a descriptive qualitative approach involving eighth-grade students as primary informants and teachers as supporting informants. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings indicate that social media functions as a flexible and interactive learning space that increases access to learning materials and student participation. However, it also creates moral challenges, including excessive gadget use, limited content filtering ability, and changes in digital communication ethics. These results highlight the need to strengthen digital literacy integrated with religious-based character education to balance academic benefits and moral risks in nonformal education settings.